Serum Level of Tumor-Overexpressed AGR2 Is Significantly Associated with Unfavorable Prognosis of Canine Malignant Mammary Tumors - Yuan, Stephen Hsien-Chi; Chang, Shih-Chieh; Huang, Yenlin; Liu, Hao-Ping (Animals (Basel), 2021)
Canine malignant mammary tumors (MMTs) are prevalent malignancy in intact female dogs with a high incidence of metastasis and recurrence. A current lack of easily accessible tumor biomarkers hinders a timely assessment of the disease outcome. We previously identified anterior gradient protein 2 (AGR2) with higher protein abundance in canine MMT tissues compared with normal counterparts. AGR2 is an endoplasmic reticulum-resident protein disulfide isomerase involved in the regulation of protein processing and also exists extracellularly via secretion to exert pro-oncogenic functions. In the present study, we validated overexpression of AGR2 in canine MMT tissues from 45 dogs using immunohistochemistry and immunoblotting, and assessed serum AGR2 levels in 81 dogs with MMTs and 21 benign cases using a competitive enzyme-linked immunosorbent assay (ELISA). Our data revealed that serum eAGR2 levels are significantly correlated with MMT progression (p = 0.0007) and remote tumor metastasis (p = 0.002). Moreover, elevated levels of serum eAGR2 are associated with an unfavorable overall survival of MMT dogs in later stage (p = 0.0158). Area under the time-dependent ROC curve (AUC) of serum eAGR2 level as a prognostic indicator was 0.839. Collectively, this study uncovered that serum eAGR2 level is significantly associated with an adverse outcome of MMT dogs and holds a predictive potential in MMT prognosis.